Severe vaso-occlusive retinopathy associated with systemic lupus erythematosus - Radosavljević, Aleksandra; Karadžić, Jelena; Kovačević, Igor; Ljikar, Jelena; Devečerski, Gordana (Vojnosanitetski pregled, 2017)
Introduction. Systemic lupus erythematosus (SLE) is a systemic idiopathic autoimmune inflammatory disease, with multiple organ involvement. Severe vaso-occlusive retinopathy is a rare, sight threatening lupus-related manifestation of the disease, which is more common in patients with coexisting antiphospholipid syndrome. Case report. We reported a 36-year-old female with severe vaso-occlusive retinopathy that manifested in the absence of antiphospholipid syndrome. In a 4-year follow-up, despite aggressive systemic corticosteroid and immunosuppressive therapy and panretinal laserphotocoagulation treatment, the disease progressed to retinal neovascularisation, neovascular vitreoretinopathy, neovascular glaucoma and, consecutively, severe visual loss. As the final option for preservation of visual function, pars plana vitrectomy with laserphotocoagulation was performed and had good results. Progression of ophthalmological findings indicated the progression of the systemic disease, as well as neurolupus. Conclusion. Severe vaso-occlusive retinopathy occurred as the ophthalmological manifestation of SLE in the absence of antiphospholipid syndrome, but correlated with neurolupus and led to visual deterioration despite the treatment.